EXPLORATION AND IDENTIFICATION OF ENTOMOPATOGEN Lecanicillium sp. WITH BAITING INSECT METHOD - Muhammad Chanif Muhtady; Inayah Fitri (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Entomopathogenic fungi are fungi that infect insects by way of entry into the body through the skin of the host insect, digestive tract and spiracles. One potential entomopathogenic fungi to control some insect pest species is Lecanicillium sp. These fungi are biological agents that effectively infect several types of insect pests, especially the order Lepidoptera, Hemiptera, Homoptera, and Coleoptera. The purpose of this study was to obtain isolates of entomopathogenic fungi Lecanicillium sp. Utilization of entomopathogenic fungi as biological control agents is one way to avoid the negative impact of chemicals on the environment. The fungus is pathogenic to various types of insects with a wide range of hosts. Entomopathogenic fungi can be obtained with the exploration of various locations with insect baiting method. fungal isolates can also be obtained through the baiting insect method.